Optimasi Penyaluran Bahan Bakar Minyak di Wilayah Maluku Indonesia - Rini Dian Sari; Farizal Farizal; Djoko Sihono Gabriel (Eigen Mathematics Journal, 2020)
Fossil fuel (BBM) is a vital commodity and has a strategic value for people's lives. On the demand side, the need for BBM tends to increase along with the increasing energy demand for people's lives. Therefore, the distribution system for BBM has to be optimized in order to fulfill the people’s demand. The aim of this paper is to optimize vehicle route for BBM distribution in Maluku so that it has minimum cost, distance, and time. The optimization method in this paper is Mix Integer Linear Programming (MILP). Decision variables in this paper are chosen from the most significant variables for BBM distribution in Maluku.